Decomposing productivity and efficiency of Western Australian grain producers - Tozer PR; Villano R (Western Agricultural Economics Association, 2013)
We provide empirical evidence to decompose productivity growth of a group of producers into technical change and efficiency measures at the farm level. Using four years of farm-level data from forty-five grain producers in the low- to medium-rainfall zone of Western Australia, we decompose productivity numbers to analyze total factor productivity. The results show that producers are generally technical, mix, and scale efficient, but the results for input and output mix efficiencies vary. The outcomes for input mix efficiency suggest that producers face some rigidity in their production decisions. In contrast, output mix efficiency suggests that most producers adjust their output mixes to account for different seasonal conditions and enterprise mixes.
Keywords: Crop production; Efficiency; Productivity